Prediction of Weyl semimetal in orthorhombic MoTe2 - Sun, Yan; Wu, Shu-Chun; Ali, Mazhar N.; Felser, Claudia; Yan, Binghai (Physical Review B - Condensed Matter and Materials Physics, 2015)
We investigate the orthorhombic phase (Td) of the layered transition-metal dichalcogenide MoTe2 as a Weyl semimetal candidate. MoTe2 exhibits four pairs of Weyl points lying slightly above (∼6meV) the Fermi energy in the bulk band structure. Different from its cousin WTe2, which was recently predicted to be a type-II Weyl semimetal, the spacing between each pair of Weyl points is found to be as large as 4% of the reciprocal lattice in MoTe2 (six times larger than that of WTe2). When projected onto the surface, the Weyl points are connected by Fermi arcs, which can be easily accessed by angle-resolved photoemission spectroscopy due to the large Weyl point separation. In addition, we show that the correlation effect or strain can drive MoTe2 from a type-II to a type-I Weyl semimetal.
CRIS-Team Scopus Importer:2023-03-20